Mentransformasi Keuangan Usaha Mikro Kecil dan Menengah: Mendongkrak Pertumbuhan Melalui Inovasi di Kabupaten Lombok Tengah - Fathurrahman; Fitri, Suci Emilia (Research and Development Agency Ministry of Home Affairs, 2024)
This study discusses the challenges faced by MSMEs. This study focuses on the importance of innovation as a transformer for micro, small, and medium enterprises, especially in the financial sector of Central Lombok Regency. The increasingly difficult challenges faced by Micro, Small, and Medium Enterprises are in Central Lombok Regency. This study uses a qualitative-exploratory approach. The study locus is Central Lombok Regency. Primary data collection was carried out using 3 (three) techniques. In-depth interviews were conducted with Micro, Small, and Medium Enterprises, the financial sector, and other stakeholders involved in Micro, Small, and Medium Enterprises activities and ecosystems. Next, observations were carried out on activities to better understand the daily operations and challenges faced by Micro, Small, and Medium Enterprises. In an effort to confirm the data and information obtained, a focus group discussion (FGD) was then carried out as part of the triangulation technique in qualitative methods. This study finds that fostering interaction among Micro, Small, and Medium Enterprises is key to their growth and sustainability. Whether through traditional partnerships or digital platforms, Micro, Small, and Medium Enterprises can benefit from coming together to increase their competitiveness and contribute to overall economic development. Apart from that, the financial transformation of Micro, Small, and Medium Enterprises through innovation opens up growth opportunities and increases competitiveness in the digital era. The government and various related parties must continue to work together to support the financial transformation of Micro, Small, and Medium Enterprises. This can be achieved by providing adequate digital infrastructure, fintech education and training programs, and regulations that support the growth of Micro, Small, and Medium Enterprises. In addition, this study recommends that the government, private sector, Micro, Small, and Medium Enterprises, and other stakeholders work together to overcome challenges and realize financial improvements for Micro, Small, and Medium Enterprises through sustainable innovation in Central Lombok Regency.